Depression, Anxiety, and Stress of Nurses\' Family Members in Covid-19 Pandemic; a Case Study of Torbat-e Heydariyeh Hospitals - T. Sarboozi-Hoseinabadi; M. Askari; Kh. Miri; M. Namazi Nia (Afarand Scholarly Publishing Institute, 2020)
Aims: Nurseschr('39') family members are among those at risk for psychological disorders caused by the Covid-19 pandemic. This study aimed to determine the rate of depression, anxiety, and stress in nurseschr('39') families in the Covid-19 pandemic. Instrument & Methods: This descriptive cross-sectional study was performed by purposive sampling from April 2016 to June 2016 with 222 family members of nurses working in the wards of patients with Covid-19 in Torbat-e Heydarieh City, Iran. Data collection tools included a demographic- and the DASS-21 standardized questionnaires. Data were analyzed using SPSS 16 software, one-way analysis of variance, and LSD post hoc test. Findings: There were significant relations between nurseschr('39') family memberschr('39') depression with marriage and relationship with the medical staff, nurseschr('39') family memberschr('39') anxiety with age group, employment status, quarantine status, and nurseschr('39') family memberschr('39') stress with employment status (p<0.05). There was a significant difference in the mean score of depression between the single/married, parents/spouse, spouse/child, and child/other groups (p<0.05). There was a significant difference in the average anxiety score between the 10 to 30 years/31 to 50 years, 31 to 50 years/51 to 70 years, plan/contract, plan/covenant, plan/company, contract/formal, return home/quarantine at home and quarantine at home/quarantine in the new house groups (p<0.05). There was a significant difference in the mean stress score between the plan/contract, plan/covenant, plan/formal, contract/corporate, and formal/corporate groups (p<0.05). Conclusion: Families of nurses working in Torbat-e Heydarieh hospitals suffer from significant levels of depression, anxiety, and stress during the Covid-19 pandemic.